REINTERPRETATION DRAFT GENDER EQUALITY IN ISLAMIC EDUCATION: A COMPARATIVE STUDY THINKING FIGURE CONTEMPORARY MUSLIM FEMINISTS - Ramlan Setiawan; Sumadi (As-Sulthan Journal of Education, 2025)
Issue gender equality in Islamic education becomes attention main in discourse contemporary Islamic feminism. This article aim For reinterpret draft gender equality in Islamic education through study comparative thinking figures contemporary Muslim feminists such as Amina Wadud, Fatima Mernissi, and Zainah Anwar. With approach qualitative based studies library, articles This explore How third figure the offer interpretation repeat to texts religious and critical structure patriarchy in system Islamic education. Study results show that reinterpretation gender concepts by the characters This open opportunity for more Islamic education inclusive and equal, without lost essence Islamic teachings.